On the Viability of Catalytic Turnover via Al−O/B−H Metathesis: The Reactivity of β‐Diketiminate Aluminium Hydrides towards CO2 and Boranes. Issue 51 (17th August 2018) - Caise, Alexa; Jones, Dafydd; Kolychev, Eugene L.; Hicks, Jamie; Goicoechea, Jose M.; Aldridge, Simon
Abstract: A series of β‐diketiminate stabilized aluminium hydrides of the type (Nacnac)Al(R)H has been synthesized offering variation in the auxiliary R substituent and in the Nacnac backbone. These show significant variation in the nature of the Al−H bond: electron‐donating R groups give rise to weaker (and presumably more hydridic) Al−H bonds, leading to enhanced rates of reactivity towards CO2 . The resulting κ 1 ‐formate complexes (Nacnac)Al(R)OC(O)H have been isolated and their reactivity towards B−H‐containing reductants probed. In the case of HBpin no reaction is observed (even under forcing conditions), while the more reactive boranes HBcat and H(9‐BBN)2 ultimately yield boryloxy complexes of the type (Nacnac)Al(R)(OBX2 ) (X2 =cat, 9‐BBN). However, no hint of Al−O/B−H metathesis is observed even under forcing conditions. With BH3 ⋅ SMe2 the major product is a related boryloxy system, although (uniquely) in this case a minor product is observed which contains an Al−H bond. We hypothesize that (Nacnac)Al(R)(κ 2 ‐BH4 ) is formed (despite the unfavourable thermodynamics of Al−O/B−H metathesis) due to the additional driving force provided by coordination of the strongly Lewis acidic BH3 unit to the Al−H bond. That said, we find that (unlike the analogous gallium systems) no catalytic turnover can be achieved in the reduction of CO2 by boranes mediated by these aluminium hydrides. Abstract : Al‐O, Al‐O, Al‐O : Mononuclear β‐diketiminate stabilized hydrides have recently been implicated in a number of reduction processes of C=O bonds. Here we show that turnover in the borane reduction of CO2 by a range of such complexes is rendered thermodynamically non‐viable by the excessive strength of the Al−O bond.